ABDUCTIVE REASONING AND THE RENEWAL OF ISLAMIC THEOLOGY: A CRITICAL ANALYSIS OF ANTI-SHĪʿĪ TENDENCIES IN INDONESIA - Ulum, Muhammad Babul; Harun , Makmur (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2025)
This study seeks to offer a renewal-oriented reading of Islamic Theology (kalām) in light of the abductive method proposed by the Indonesian thinker Amin Abdullah, as an alternative approach capable of breaking the epistemic stagnation in advanced Islamic studies and overcoming the epistemological impasse inherited by classical kalām from the medieval period. The study further attempts to employ this method in analyzing the rise of anti-Shīʿī tendencies in Indonesia, viewing them as a model of theological–political conflict reproduced within the local context. Adopting a comparative critical-analytical approach, the study concludes that the renewal of kalām cannot be achieved except through a re-reading of the theological tradition in light of contemporary social and political realities, alongside the integration of abductive reasoning, which enables intellectual flexibility and multiplicity of hypotheses without falling captive to sectarianism or exclusionary dogmatism.